An Analysis Authentic Assessment On Speaking Abilities In English Classroom - Siregar, Siti Saidah; Zulkifli, Nur Aisyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The authentic assessment as the measurement method to evaluate students’ learning objectives and achievements in the classroom. The application of authentic assessment requires teachers to evaluate students’ in three competencies: attitude, knowledge, and skill. Most teachers and educator said that speaking is the most difficult skill to be assessed by using the authentic assessment, considering the complex features of the assessment. This research was aimed at describing the application of authentic assessment in a speaking classroom which relates to the types of the assessment and the scoring rubric. The subjects of the study were an English teacher and 34 students of the SMK Muhammadiyah 3 Pekanbaru. Descriptive qualitative approach was applied in this research, the data in this study was obtained from observation and document analysis. The results of the study revealed that the teacher used several types of activities to assess students’ speaking skills: (1) attitude assessment , (2) knowledge assessment, and (3) skill assessment. The result of this study indicates that authentic assessment is a feasible way to assess students’ speaking skill and it should be employed in assessing other skills as well for learning languages.